2016
DOI: 10.1038/srep27875
|View full text |Cite|
|
Sign up to set email alerts
|

58-F, a flavanone from Ophiopogon japonicus, prevents hepatocyte death by decreasing lysosomal membrane permeability

Abstract: Lysosome membrane permeabilization (LMP) has been implicated in cell death. In the present study, we investigated the relationship between cell death and H2O2-/CCl4-induced LMP in hepatocytes in vitro and following acute liver injury in vivo. The key finding was that H2O2 triggered LMP by oxidative stress, as evidenced by a suppression of LAMP1 expression, a reduction in LysoTracker Green and AO staining, and the leakage of proton and cathepsin B/D from the lysosome to the cytoplasm, resulting in cell death. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 40 publications
(47 reference statements)
0
5
0
Order By: Relevance
“…Confirming these observations, the ultrastructure of infected Rab20 KO BMM more often showed multiple p62-labeled host-derived membranes and vesicles in close proximity to Mtb compared with WT BMM ( Figure 4 D). To monitor phagosome integrity dynamics in macrophages, we used LysoTracker as a probe that, after irreversible protonation, gets trapped into the lumen of acidic compartments ( Yan et al., 2016 ). We observed that Mtb phagosomes became leaky for LysoTracker at different stages in WT BMM and fusion with endosomes restored LysoTracker levels within phagosomes ( Figures 4 E–4G; Movie S3 ).…”
Section: Resultsmentioning
confidence: 99%
“…Confirming these observations, the ultrastructure of infected Rab20 KO BMM more often showed multiple p62-labeled host-derived membranes and vesicles in close proximity to Mtb compared with WT BMM ( Figure 4 D). To monitor phagosome integrity dynamics in macrophages, we used LysoTracker as a probe that, after irreversible protonation, gets trapped into the lumen of acidic compartments ( Yan et al., 2016 ). We observed that Mtb phagosomes became leaky for LysoTracker at different stages in WT BMM and fusion with endosomes restored LysoTracker levels within phagosomes ( Figures 4 E–4G; Movie S3 ).…”
Section: Resultsmentioning
confidence: 99%
“…4G,H). Recently, a flavanone, 5,8-dimethoxy-6-methyl-7-hydroxy-3-3(2-hydroxy-4-methoxybenzyl) chroman-4-one (58-F), extracted from Ophiopogon japonicas has been reported to play a similar role (Yan et al, 2016). This flavonoid protects the H 2 O 2 -induced damage in hepatocytes by decreasing the calcium concentration and suppressing the PLCγ1-IP 3 R-SOC pathway, leading to reduced HMGB1 release.…”
Section: Discussionmentioning
confidence: 99%
“…The suspension was incubated with Annexin V-kFluor488 and stained with PI (Kaiji Biology Corp., China) at room temperature for 20 minutes and then analyzed on flow cytometer (Cyto Flexz, Beckman, USA). The annexin V-positive/PI-negative cells indicated apoptotic cells at the early period, and the annexin V-positive/PI-positive cells showed those at the later period [ 36 ]. The ratio of apoptosis or apoptosis index (AI) was calculated using the following equation: …”
Section: Methodsmentioning
confidence: 99%